P101 From research to practice: implementing a quality self-management pulmonary rehabilitation programme. (December 2018) - Chaplin, E; Bourne, C; Singh, S
Abstract : Introduction: Implementing change within existing services should follow pragmatic or exploratory trials. It requires substantial effort and typically needs to be driven by enthusiasm. Research studies and national audits have highlighted Pulmonary Rehabilitation (PR) quality standards are not being met and suggest alternative, remote, modes of delivering PR for patients unable to attend traditional hospital-based classes should be provided. Methods: A knowledge translation principle was applied to implement the home-based SPACE for COPD self-management programmes (manual and website) into routine clinical practice, allowing clinicians to offer alternative modes of delivery and stratifying patient care. Patients were eligible to partake in the home-based programmes if they were COPD and MRC 2–5; for the WEB programme, patients needed to be computer literate. Exclusion criteria were as per normal PR protocol. PR staff were trained in motivational interviewing and delivery of the manual or website. Initially 1 staff member was responsible for each arm of the home-based programmes whilst training was cascaded. Routine clinical outcomes were analysed to measure effectiveness of translation from research to clinical service. Results: During April 2017–2018, 620 patients were suitable for a home-based PR programme (i.e. attended a PR assessment and were COPD); 8% (n=53) chose home-based PR due to anxiety around group settings, work or other commitments. 47% (n=25) completed the programme. See table 1 for baseline characteristics. Changes in quality of life and exercise capacity were clinically meaningful. However, only changes in walking tests and self-efficacy were statistically significant (p≤0.05) which reflect research results. Difficulty contacting patients meant there were a high proportion of dropouts. Algorithms were applied to manage patients and standardised contact sheets used. A small group of patients completed their PR programmes by transferring from home-based to supervised classes and vice versa. Staff engagement increased once results showed positive trends. All values are mean (±SD) unless otherwise stated. Abbreviations: FEV1, forced expiratory volume in 1 s; L, litres; FVC, forced vital capacity; MRC, Medical Research Council; IQR, interquartile range; ISWT, Incremental shuttle walk test; m, metres; ESWT, Endurance shuttle walk test; sec, seconds; HADS –A, hospital anxiety and depression score – anxiety; HADS –D, hospital anxiety and depression score – depression; CAT, COPD assessment tool; CRQ-SR Chronic Respiratory disease Questionnaire – Self Report; PRAISE, Pulmonary Rehabilitation Adapted Index of Self-Efficacy; BCKQ, Bristol COPD Knowledge Questionnaire. Discussion: There are always challenges around implementing change into an established service with both physical constraints and work force engagement. Initial analysis of the service change shows promising results with improvements in quality of life and exercise capacity, the latter being comparable if not better than results seen in corresponding research studies.